Investigation of uranium sorption from acidic sulfate solution using organosilicate compound and Amberlite IRA 402 - Kouraim, Mohamed Nouh; Sheta, Mohamed El Said; Abd Elaal, Mostafa Mahmoud (European Journal of Chemistry, 2014)
Sorption of uranium from 6 M free H2SO4 on two anionic sorbents containing different complexing groups, the synthetic Organosilicate compound (OSC) and the Amberlite IRA 402, were investigated. The sorption mechanisms of uranium on both sorbents were also studied. Experimental data indicated that the uranium sorption on either Amberlite IRA 402 or OSC is a function in pH, depending strongly on the aqueous uranyl species. Both sorbents reached a maximum at slightly acidic (pH = 1) when uranium is exist in the form of negatively charged sulfate complexes. These sorption values were attributed to the ion exchange process between UO2+2 species and interlayer anions on Amberlite IRA 402 and OSC in acidic solutions. Uranium sorbed on OSC through formation of ML3 complex and ML2 for Amberlite IRA 402. Also it was found that the uranium sorption capacity was 20 and 80 mg/g for Amberlite IRA 402 and OSC, respectively, and its elution were effective even with 5 mL of 1 mol/L KNO3.